Sistem Pendaftaran Hotspot Online Berbasis Web Menggunakan Mikrotik API, PHP, MySql Pada SMK Plus Nurul Hakim Kediri - Lalu Yusran Said; Andy Hidayat Jatmika; I Wayan Agus Arimbawa (Program Studi Teknik Informatika, Fakultas Teknik, Universitas Mataram, 2019)
Abstract Now days the use of internet access is a priority for everyone. One of the internet media that is often used today is a hotspot network. Hotspot use at vocational high school (SMK) plus nurul Hakim using Indiehome wifi router. By default the hotspot security on this device uses a single password for all users connected to this hotspot network. This causes the security of the hotspot network is not safe, inefficient time and increases the workload of the Hotspot manager to change password at every change. Based on these problems, research is conducted that aims to create a web-based online hotspot registration system by using the PHP Programming Language, MikroTik PHP Class API, and MySQL Database. The results of this study are expected to be a solution to overcome the problem of hotspot service on vocational high school plus nurul Hakim kediri. If utilizing this hotspot registration system will help users register quickly. Keywords words: system register hotspot, API Mikrotik, PHP, MysQl, Mikrotik.